Cochrane Database of Systematic Reviews 2015
DOI: 10.1002/14651858.cd007025.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing for alcohol misuse in young adults

Abstract: The editorial group responsible for this previously published document have withdrawn it from publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(58 citation statements)
references
References 103 publications
1
54
1
2
Order By: Relevance
“…With the exception of peak blood alcohol concentration immediately postintervention ( d = 0.36), the average effect size ranged from d = 0.11 to 0.22 across all outcomes. In addition, a recent meta‐analysis (Foxcroft et al., ), which focused on MI versus no MI for alcohol misuse among adolescents and emerging adults between the ages of 15 and 25, similarly concluded that the effect sizes were quite small. Thus, these existing meta‐analyses and narrative reviews collectively suggest that if effects of college alcohol interventions are statistically significant, they are generally small, even in the short term.…”
Section: Meta‐analysis Using Individual Participant‐level Datamentioning
confidence: 99%
“…With the exception of peak blood alcohol concentration immediately postintervention ( d = 0.36), the average effect size ranged from d = 0.11 to 0.22 across all outcomes. In addition, a recent meta‐analysis (Foxcroft et al., ), which focused on MI versus no MI for alcohol misuse among adolescents and emerging adults between the ages of 15 and 25, similarly concluded that the effect sizes were quite small. Thus, these existing meta‐analyses and narrative reviews collectively suggest that if effects of college alcohol interventions are statistically significant, they are generally small, even in the short term.…”
Section: Meta‐analysis Using Individual Participant‐level Datamentioning
confidence: 99%
“…This time frame was used to capture information between each assessment to provide a more continuous measure of use across time. Four-month windows for substance use have been used in other studies to capture a broader window of use (Donohue, Holland, Lopez, Urgelles, & Allen, 2014; Foxcraft et al, 2014; Halkitis, Palamar, & Mukherjee, 2007). Analyses conducted in this article with four-month vs. 30-day windows yielded highly similar findings.…”
Section: Methodsmentioning
confidence: 99%
“…1 The Cochrane review authors agree with prior reviews that there are statistically significant effects in reducing alcohol misuse, but interpret the effects as “too small …to be of relevance to policy and practice.” 1 In this issue of Addiction , Grant and colleagues question that conclusion. They point out that single-touch, low-cost brief motivational interviewing-based interventions (BIs)—if widely implemented—can have “modest yet beneficial and potentially meaningful” population-level effects.…”
mentioning
confidence: 87%
“…3 Of the 66 trials included in the Cochrane review, 49 consisted of a single session and only 5 included more than 2 contacts. 1 In contrast to the 1 in 9 adult patients with alcohol misuse who respond to a single BI, 1 in 4 respond to four sessions of BI. 7 Repeated BIs have been found effective in several studies of adult patients with AUDs, 810 including a large BI trial, which demonstrated changes in patient-report of hospital utilization.…”
mentioning
confidence: 98%
See 1 more Smart Citation